Effectiveness of oral health education on oral hygiene status among schizophrenic patients: A randomized controlled study. (12th March 2019) - Agarwal, Deepali; Kumar, Adarsh; B.C., Manjunath; Sethi, Sujata; Yadav, Vipul; Shyam, Radhey; Kumar, Vijay
Abstract: Aim: The study aims to assess the effectiveness of oral health education on oral hygiene status among schizophrenic patients. Methods and results: A randomized parallel controlled trial was conducted among schizophrenic patients (n = 111) with BPR score of ≤ 48 to assess the role of oral health education on their oral hygiene status. The experimental group (n = 56) received oral health education while the control group (n = 55) were administered standard care advice. Reinforcement in the form of printed calendar was done after 1 month followed by final assessment of KAP (knowledge, attitude and practice) through DCBS (Dental Coping Beliefs Scale), while oral hygiene through the oral hygiene index done after 2 months. Majority of subjects were males with mean age of 34.73 ± 9.9 years and mean duration of illness of 6.41 ± 5.2 years. All domains of the modified DCBS showed significant improvement in the experimental group. Frequency of brushing twice a day increased from 5.4% to 23.2% ( p  < 0.05) in the experimental group. DI score was 2.28 ± 0.93 versus 2.98 ± 1.3 ( p  < 0.02) in the experimental group as compared to the control group. Conclusion: The oral health education with reinforcement in the form of printed calendar although showed statistically significant changes but lacked clinical importance.